2001
DOI: 10.1001/archpsyc.58.5.427
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain and Ventricular Volumes in Tourette Syndrome

Abstract: Background:The pathophysiology of Tourette syndrome (TS) is thought to involve disturbances in corticostriato-thalamo-cortical circuitry. The morphological characteristics of the cortical and associated white matter portions of these circuits have not been previously examined in TS subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
221
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 278 publications
(246 citation statements)
references
References 80 publications
22
221
0
3
Order By: Relevance
“…A number of patients in the present study were taking psychotropic medication, which could potentially have influenced the results. This seems unlikely, however, as MRI studies of other patient groups taking similar medications to those used in patients with autism have not reported reductions in the size of the lateral ventricles (Kumra et al, 2000;Peterson et al, 2001;Scherk and Falkai, 2006). Additionally, control subjects in the present study did not differ on traditional ventricular measures from patients receiving medication and medication-free patients, further suggesting that the results of this study are not solely due to the effects of psychotropic medication.…”
Section: Discussionmentioning
confidence: 47%
“…A number of patients in the present study were taking psychotropic medication, which could potentially have influenced the results. This seems unlikely, however, as MRI studies of other patient groups taking similar medications to those used in patients with autism have not reported reductions in the size of the lateral ventricles (Kumra et al, 2000;Peterson et al, 2001;Scherk and Falkai, 2006). Additionally, control subjects in the present study did not differ on traditional ventricular measures from patients receiving medication and medication-free patients, further suggesting that the results of this study are not solely due to the effects of psychotropic medication.…”
Section: Discussionmentioning
confidence: 47%
“…Our recent anatomical study of TS, for example, reported increased volumes of dorsal prefrontal and parietal cortices and reduced volumes of inferior occipital regions in subjects with TS compared with normal controls (8,9). In addition, published reports indicate that children with TS have a smaller CC than do normal controls (36).…”
Section: Methodsmentioning
confidence: 89%
“…We propose that the larger P300 amplitude observed in the GTS group could be attributable to overactivation of specialized cortical areas. Hyperactivation of the dorsolateral region has been demonstrated to be involved in GTS by past fMRI studies (Peterson et al, 2001). The magnitude of signal change in the dorsolateral prefrontal cortex was found to be positively correlated with tic severity and its greater activation was also found to be associated with regulation of performance in complex attentional tasks in participants with GTS (Marsh et al, 2007).…”
Section: Effect Of Gilles De La Tourette Syndrome On Erp Profilementioning
confidence: 87%